Barriers to retention in methadone maintenance therapy among people who inject drugs in Bangkok, Thailand: a mixed-methods study - Hayashi, Kanna (Harm Reduct J, 2017)
BACKGROUND: Methadone maintenance therapy (MMT) is a mainstay for treating opioid use disorder and preventing and managing HIV among people who inject drugs (PWID). While previous research suggested low dosing of methadone and high rates of discontinuation of MMT among PWID in Thailand, little is known about patients’ lived experiences with MMT in this setting. Therefore, we conducted a mixed-methods study to examine barriers to retention in MMT among PWID in Bangkok, Thailand, with particular attention to methadone dosing. METHODS: Bivariate statistics were used to analyze quantitative survey data collected from methadone-treated PWID between July and October 2011. Qualitative data collected through semi-structured interviews with 16 methadone-treated PWID between July 2011 and June 2012 were analyzed thematically, with a focus on individual-level, social-structural, and environmental barriers to accessing MMT. RESULTS: Among 158 survey participants, a median dosage of methadone was 30 mg/day (interquartile range 20–50). Of these, 15.8% reported having acquired street methadone due to low prescribed dosages of methadone and 19.0% reported recent syringe sharing. Qualitative interview data indicated some methadone provider-related barriers, including discouraging patients from using methadone due to it being a Western medicine, difficulty negotiating higher doses of methadone, and abrupt dose reductions without patient consultation (involving the provision of non-medicated “syrup” in some cases). Social-structural and environmental barriers to optimal MMT access included intense police surveillance of methadone clinics; and frequent incarceration of PWID and a lack of access to methadone in prisons. CONCLUSIONS: Among our sample of methadone-treated PWID, methadone dosages were suboptimal according to the international guidelines. Poor adherence to international guidelines for opioid agonist therapies, aggressive law enforcement, and a lack of methadone in prisons need to be addressed to optimize MMT and reduce harms associated with untreated opioid use disorder in Thailand.